Development of Decodable Books to Improve the Beginning Reading Skills of Reading Disabilities Students at Primary Schools in Malang - Sushanty, Resty; Valentina, Triya; Putri, Karinda Devinta; Billy, Bill; Arsanti, Syalia Nazhiyan; Novianti, Ranti; Pradipta, Rizqi Fajar (Department of Special Education, 2024)
Reading disabilities are someone who experience obstacles in their phonological processes such as identifying letters, distinguishing letter sounds, and their pronunciation, thereby affecting academic development factors, especially aspects of reading. Decodable books can be deciphered and contain code-based phonics learning. This research aims to develop and validate the Decodable book according to the characteristics and needs of students with reading disabilities. This research uses the ADDIE RnD model (Analysis: analysis of needs and characteristics of the subject, Design: design according to initial analysis, Development: design development, Implementation: media application, and Evaluation: evaluation of the entire process). The subjects of this research were 4 students with reading disabilities criteria at elementary schools in Malang City. Data analysis of needs and subject characteristics was obtained through interviews with teachers and carrying out identification tests and assessments. The results of this research produced Decodable book (Decobo) which media experts and material experts have validated with an average score of 78.6% in the valid category with minor revisions. Decodable book (Decobo) was developed into an e-book packaged as an application with three levels of word pattern books (VC-V, CV-CV, CV-C). Decodable book (Decobo) has been applied to subjects with an overall score of 72.60%. The category is quite effective in improving the initial reading abilities of students with reading disabilities. This research still needs further development and testing on a wider scale.